Breast Cancer Metastasis and Drug Resistance Progress and Prospects - Ahmad, Aamir (Springer New York : Imprint: Springer, 2013)
This comprehensive book on breast cancer brings together some of the leading experts in an attempt to better understand breast cancer disease, the factors that make it lethal and current research progress, integrating both basic research with clinical implications. This volume covers the following core issues: i) heterogeneity in breast cancer - statistics, epidemiology, breast cancer subtypes, racial disparity and the associated challenges, ii) available and upcoming model systems in breast cancer research, iii) breast cancer metastasis to bones and brain, iv) drug resistance mechanisms in breast cancer against targeted therapies and v) recent developments in breast cancer research - state of current research directions / technologies / approaches. With its comprehensive coverage of topics related to breast cancer, this volume is expected to have a very wide appeal. It serves as an excellent source of reference for students/beginning researchers just setting foot in the field and interested in getting to know all the aspects of this disease. The book should also appeal to advanced and senior researchers by bringing everyone up-to-date with the most current knowledge on various breast cancer topics of utmost relevance.